Potensi Penambahan Serat Alumina dalam Kaca Optik sebagai Doping untuk Aplikasi Light Detection and Ranging (LIDAR) - Djuliana, Safiya; Aritonang, Sovian; Muniarti, Riri (Fakultas Teknik UMSU, 2024)
The optical glass used in LiDAR applications requires specific characteristics, including high strength and low porosity, to achieve optimal performance. One promising approach is the incorporation of alumina fibers as a reinforcement in the optical glass matrix. This research investigates the potential of alumina fibers in enhancing strength and reducing porosity in optical glass used in LiDAR applications. Alumina fibers are introduced into the optical glass matrix through a precise manufacturing process. The results of mechanical testing indicate that the addition of alumina fibers significantly increases the strength of the optical glass, making it more resistant to mechanical pressure that may occur during the use of LiDAR in challenging environments.